Inter-Media Publishing System (IMPSYS) for classified advertising service providers / WanYuee Low - Wan, Yuee Low (UiTM Press, 2015)
With the recent development of digital media, Classified Advertising Service Providers often face problems in managing advertisement requirements in terms of advertising requirements and production expertise. As an advertiser, placing an advertisement requires a lot of effort in understanding “what are you paying for” since there are discretely different advertising schedules and designs to contend with across different medias. Classified Advertising Magazines generally features very little content and more advertisements, therefore the subscription rate of these type of magazines are low. The Inter-Media Publishing System aims to simplify the classified advertising process by providing the publisher an online tool to collect and manage advertisements, which will then be placed into an easy readable magazine format. Advertisers can benefit from being able to manage their advertisements and communications right from the desktop & mobile app. Magazine subscribers can preview and access the library of online magazines and browse suggested content using the application, while potential customers can benefit from a streamlined process of trading with real time communications and bookmarking facilities on the same application. The end product is a new online service provides a cost effective way for advertisers access to a bigger marketplace through content marketing.